Acesso ao tratamento oncológico no SUS: a responsabilidade civil do Estado pela perda da chance de cura ou de sobrevida das pacientes com câncer de mama no Rio Grande do Sul - Finger, Brunize Altamiranda (Universidade do Vale do Rio dos Sinos, 2017)
The dissertation aims to verify if the State can be held civilly responsible, and under what conditions, for the loss of the chance of cure or survival of patients with breast cancer who did not have access to medical treatment by the SUS within 60 days after diagnosis - term established by Law 12.732/2012. For that, the phenomenological-hermeneutic method and the inductive method were used. From (i) data collected in the RHC Integrator about the time interval between diagnosis and first medical treatment, (ii) bibliographical research on the scarcity of financial and non-financial resources, and (iii) research on the peculiar trajectory of the Brazilian Welfare State, it was concluded that the State can be held liable for the loss of the chance of cure or survival. The applicability of the theory of objective liability to such cases is defended. However, before imputation of this responsibility, it is necessary to evaluate three factors: Universality of access to treatment against breast cancer in up to 60 days, Treatment against breast cancer materially possible and Accessibility to medical treatment against geographical barriers.
Keywords: Direito à saúde; Responsabilidade civil do Estado; Dano pela perda da chance; Câncer de mama; Right to health; Civil liability of the state; Damage to loss of chance; Breast cancer; ACCNPQ::Ciências Sociais Aplicadas::Direito